How can point-of-care HbA1c testing be integrated into UK primary care consultations? – A feasibility study - Hirst, J; Stevens, R; Smith, I; James, T; Gudgin, B; Farmer, A (Elsevier, 2017)
Aims Point-of-care (POC) HbA1c testing gives a rapid result, allowing testing and treatment decisions take place in a single appointment. Trials of POC testing have not been shown to improve HbA1c, possibly because of how testing was implemented. This study aimed to identify key components of POC HbA1c testing and determine strategies to optimise implementation in UK primary care. Methods This cohort feasibility study recruited thirty patients with type 2 diabetes and HbA1c >7.5% (58mmol/mol) into three primary care clinics. Patients’ clinical care included two POC HbA1c tests over six months. Data were collected on appointment duration, clinical decisions, technical performance and patient behaviour. Results Fifty-three POC HbA1c consultations took place during the study; clinical decisions were made in 30 consultations. Five POC consultations with a family doctor lasted on average 11 minutes and 48 consultations with nurses took on average 22 minutes. Five POC study visits did not take place in one clinic. POC results were uploaded to hospital records from two clinics. In total, sixty-four POC tests were performed, and there were 11 cartridge failures. No changes in HbA1c or patient behaviour were observed. Conclusions HbA1c measurement with POC devices can be effectively implemented in primary care. This work has identified when these technologies might work best, as well as potential challenges. The findings can be used to inform the design of a pragmatic trial to implement POC HbA1c testing.